2016
DOI: 10.3390/molecules21060710
|View full text |Cite
|
Sign up to set email alerts
|

The Hedyotis diffusa Willd. (Rubiaceae): A Review on Phytochemistry, Pharmacology, Quality Control and Pharmacokinetics

Abstract: Hedyotis diffusa Willd (H. diffusa) is a well-known Chinese medicine with a variety of activities, especially its anti-cancer effect in the clinic. Up to now, 171 compounds have been reported from H. diffusa, including 32 iridoids, 26 flavonoids, 24 anthraquinones, 26 phenolics and their derivatives, 50 volatile oils and 13 miscellaneous compounds. In vitro and in vivo studies show these phytochemicals and plant extracts to exhibit a range of pharmacological activities of anti-cancer, antioxidant, anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 54 publications
2
75
0
Order By: Relevance
“…Traditionally, it is used for the treatment of bronchitis, arthritis, rheumatism, urethral infection, appendicitis, sore throat, contusions, ulcerations and extension of malignancies [10]. Modern pharmacological studies have proved that H. diffusa have multiple effects, such as anti-inflammatory, anti-cancer, immunemodulating, neuroprotective and hepatoprotective activities [11]. It was found that the iridoid compounds possibly attributed to anti-inflammatory effect of H. diffusa [12][13].…”
Section: Hedyotis Diffusa Willd As a Famous Traditional Chinese Medicmentioning
confidence: 99%
“…Traditionally, it is used for the treatment of bronchitis, arthritis, rheumatism, urethral infection, appendicitis, sore throat, contusions, ulcerations and extension of malignancies [10]. Modern pharmacological studies have proved that H. diffusa have multiple effects, such as anti-inflammatory, anti-cancer, immunemodulating, neuroprotective and hepatoprotective activities [11]. It was found that the iridoid compounds possibly attributed to anti-inflammatory effect of H. diffusa [12][13].…”
Section: Hedyotis Diffusa Willd As a Famous Traditional Chinese Medicmentioning
confidence: 99%
“…The components of iridoids, triterpenes, flavonoids, lignans, anthraquinones, alkaloids, cerebrosides, coumarins, and sterols were discovered during the chemical studies of H. diffusa Willd. [ 2 , 6 , 7 , 8 ]. There are some differences of the chemical constituents if the H. diffusa Willd.…”
Section: Introductionmentioning
confidence: 99%
“…These include 2,7-dihydroxy-3-methyl anthraquinone, 2-hydroxy-3-methyl-1-methoxy anthraquinone, 2-hydroxy-3-methoxy-7-methoxy anthraquinone, 2-methyl-3-hydroxy anthraquinone, 2-methyl-3-hydroxy-4-methoxy anthraquinone, deacetyl asperulosidic acid, scandoside, E -6- O - p -coumaroyl scandoside methyl ester [ 9 ]. Various hepatoprotective, immunoloregulation, anti-tumor, anti-inflammatory, antibacterial, analgesia, sedative, and anti-oxidant activities can be found in pharmacological studies of H. diffusa Willd [ 3 , 6 , 10 , 11 , 12 , 13 ], but more studies found that the extracts from H. diffusa Willd. possessed evident anticancer activities [ 1 , 2 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hedyotis diffusa willd and some of its active constituents have gained increasing attention as an antitumor herb. Clinically, this herb has often been applied as a critical element in many TCM formulae for the treatment of various cancers, including gastric cancer (GC) and colorectal cancer (61)(62)(63)(64). A latest retrospective matched-cohort study presented that Hedyotis diffusa willd was the most commonly prescribed single herb for treating GC patients and complementary TCM therapy enhanced the overall survival of patients with GC in Taiwan (62).…”
Section: Some Single Tcms With Properties Of Clearing Heat and Detoximentioning
confidence: 99%
“…A latest retrospective matched-cohort study presented that Hedyotis diffusa willd was the most commonly prescribed single herb for treating GC patients and complementary TCM therapy enhanced the overall survival of patients with GC in Taiwan (62). It probably produced the therapeutic effects against GC by synergistically regulating many biological pathways, such as nucleotide excision repair, apoptosis, cell cycle, PI3K/AKT/mTOR signaling pathway, VEGF signaling pathway, and Ras signaling pathway (61). Hedyotis diffusa willd could suppress colorectal cancer growth through multiple cellular pathways including MAPK, STAT3, AKT and ERK signaling (63).…”
Section: Some Single Tcms With Properties Of Clearing Heat and Detoximentioning
confidence: 99%